Texture and magnetic anisotropy of YBa2Cu3O7-x film on MgO substrate - Cornejo H.S. (2020)
The texture and magnetic anisotropy of a YBa2Cu3O7-x (YBCO) film growth onto a MgO substrate are analyzed in order to understand the relation between them. X-ray diffraction shows the presence of the (00l) reflections from the YBCO layer with a grain’s fraction value 98%. Rocking Curves (RC) measurements reveal an out-of-plane texture with a full width at the half maximum of 0.81°, revealing a high uniaxial texture in the YBCO film. The temperature dependence of the susceptibility measurements obtained under many applied fields along Hext